Abundance and Characterization of Microplastics in Main Urban Ditches Across the Bahir Dar City, Ethiopia - Mhiret Gela, Sahlu; Aragaw, Tadele Assefa (Frontiers in Environmental Science, 2022)
Microplastics (MPs) pollution in water bodies, wastewater, and sewage is of concern due to their probable effects on the environment and human health. This study is a first-time attempt to evaluate MPs occurrence, abundance, characteristics, and polymeric types in sediment and agglomerated sewage water from several urban ditches in Bahir Dar, Ethiopia, in two class sizes (> 0.5 and < 0.5 mm). Out of the total of 239 MP particles, 61.09% were of <0.5 mm and this dominant fraction was transparent and consisted of fragmentary shapes. The mean abundances of <0.5 mm particles were 5 ± 1.00 items/50 g in sediment and 3.00 ± 1.00 items/ml in agglomerated sewage water. Similarly, the abundances of >0.5 mm fractions were 2.33 ± 0.58 items/50 g in sediment and 1.33 ± 0.58 items/50 ml in Agglomerated sewage water. Polyethylene (PE), Polypropylene (PP), polyethylene terephthalate (PET), Polystyrene (PS), polyamide (PA), and polyvinylchloride (PVC), were the most detected plastics. However, PET and PVC were not detected in the agglomerated sewage water samples.